(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In the present article, the author draws on some central concepts of psychoanalysis, such as the “enigma of sexuality” and the “family romance,” for an autoethnographic exercise that takes gender issues and the territory of scene and performance as focuses of work and experience. She primarily delves into the concept of the “feminine masquerade” by psychoanalyst Joan Rivière to think about gender performativity in its symptomatic dimension, adopting, through the affiliation with the author Julia Kristeva, an abject perspective.